Skrining Fitokimia Dan Uji Aktivitas Antibakteri Ekstrak Daun Matoa (Pometia pinnata J.R.Forst & G.Forst) Terhadap Bakteri Staphylococcus aureus dan Staphylococcus epidermidis - Dewi, Asiska Permata; Shufyani, Fahma; Putriani, Kony (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2025)
The matoa plant (Pometia pinnata J.R.Forst & G.Forst) is an Indonesian plant that has many benefits, one of which is as an antibacterial. The purpose of this study was to determine the content of secondary metabolite compounds found in matoa leaves and test their antibacterial activity against Staphylococcus aureus and Staphlococcus epidermidis bacteria. The extraction method used in this study is the maceration method using ethanol as a solvent and antibacterial activity testing using the disc diffusion method. Secondary metabolites found in matoa leaves extract are flavonoids, saponins, tannins and steroids. The antibacterial activity of matoa leaf ethanol extract against Staphylococcus aureus bacteria at concentrations of 10%, 20%, 30% and 40% obtained an average diameter of the inhibition zone of 11.0 mm; 11.4 mm; 11.0 mm and 13.3 mm. Then the average diameter of the inhibition zone in Staphylococcus epidermidis bacteria was 13.2 mm; 14.0 mm; 13.9 mm and 14.1 mm This study proves that matoa leaves have a strong antibacterial effect against Staphylococcus aureus and Staphlococcus epidermidis bacteria.